Reconfigurable snap-together sculpting. Issue 1 (2nd January 2016) - Séquin, Carlo H.
ABSTRACT: A mixture of general-use and of some custom-designed plastic parts, fabricated on inexpensive layered manufacturing machines, is used to construct a variety of sculptural maquettes. This article describes the design and fabrication of a set of modular parts that permit the assembly of tubular sculptures as well as constructivist realizations of mathematical knots and links. GRAPHICAL ABSTRACT: